Synthesis and aggregation properties of polycationic perylenetetracarboxylic acid diimides - Schönamsgruber, Jörg; Schade, Boris; Kirschbaum, Rolf; Li, Jing; Bauer, Walter; Boettcher, Christoph; Drewello, Thomas; Hirsch, Andreas (European Journal of Organic Chemistry, 2012)
The synthesis and structural characterization of a first family of dendronized polycationic perylenetetracarboxylic acid diimides (PDIs) 7, 8, and 10 is reported. They were obtained by amide coupling reactions of pyridinium salt head groups with terminal carboxylic groups of Newkome-dendron-type functionalized PDIs. Resulting pyridinium-terminated PDIs 7, 8, and 10 are highly water-soluble, independent of the pH value. This is due to 6, 18, and 9 permanent positive charges, respectively. PDIs 7 containing the smaller first-generation dendrons exhibit a pronounced aggregation behavior in water. This was studied by absorption and fluorescence spectroscopy, by pulsed-gradient spin-echo (PGSE, DOSY) NMR measurements, and by cryo-transmission electron microscopy (cryo-TEM). The counterparts containing the bulkier second-generation dendrons hamper aggregation, and as a consequence intermolecular π-π stacking interactions between the perylene cores is suppressed. © 2012 Wiley-VCH Verlag GmbH & Co. KGaA, Weinheim.